Bentuk Profil Subsektor Teh Indonesia dan Lanskap Persaingan Produksi dan Perdagangan Teh Dunia pada Masa Datang - Ibnu, Muhammad (National Research and Innovation Agency, 2024)
Identifying the Indonesian tea commodity subsector profile can help us better understand various challenges and problems related to production and trade. The research aims to (a) identify the profile of the Indonesian tea commodity subsector, (b) analyze the forces that influence the tea subsector profile, and (c) predict the competitive landscape of tea production and trade in the future. The research used qualitative (literature review) and quantitative methods through time series analysis with FAOSTAT data from 1961 to 2022. The results showed that the tea commodity subsector profile combines a pyramid and a diamond. The forces that influence the shape of the tea subsector are production and market characteristics, enabling environment, and sources of livelihood. These forces do not work separately but interact with each other. The world tea production surplus is predicted to increase, implying that prices will decrease. In addition, Indonesian tea in the world market faces the risk of increasingly tight competition with lower price levels. To improve the sustainability of Indonesian production and trade, a combination of various policy instruments or programs, such as public and private investment policies in education, infrastructure development, and work facilities, and to increase the participation of all stakeholders, is needed.